Injectable Bone Substitute Paste Based on Hydroxyapatite, Gelatin and Streptomycin for Spinal Tuberculosis - hendita maulida (Stem Cell Research and Development Center, Universitas Airlangga, 2020)
World Health Organization (WHO) in 2005 reported that cases of tuberculosis (TB) in the world occur more than 8 million annually and 5-10% were attacked in spine. The most effective treatment of spinal TB is evacuation of infected bone segments and fill with bone graft. It has been synthesized and characterized of injectable bone substitute (IBS) paste based on hydroxyapatite, gelatin and streptomycin. IBS paste synthesized by mixing hydroxyapatite and gelatin 20% w/v with 75:25, 70:30, 65:35 and 60:40 ratio and streptomycin 10 wt%. The mixture was then added with hydroxypropyl methylcellulose (HPMC) 4% w/v as suspending agent. In vitro characterization performed include acidity (pH), injectability test, setting time, cytotoxicity (MTT assay) and microbacterium test. Acidity test results indicate a fourth variation of the samples had pH values approaching normal body pH (7,3 to 7,6) and is able to maintain stability when measured in 7 days. Injectability test results indicate IBS paste is injectable with the highest percentage of the injectability value at 97,74% ± 0,19%. IBS paste has been setting within 30 minutes to 1 hour when injected on hydroxyapatite scaffold that resembles the bone cavity and is able to cover the pore scaffold seen from the Scanning Electron Microscope (SEM). Scaffold pore size is smaller from range of 780,8 to 835,4 μm into 225,2 μm. MTT assay results showed that IBS paste is not toxic and experiencing proliferation (viability >100%) that are expected to trigger osteoblast cell growth when applied. Microbacterium test results showed that IBS paste is an antibacterial seen from inhibition zone diameter of Staphylococcus aureus and has a high strength-sensitive antibacterial. Thus, hydroxyapatite, gelatin and streptomycin composites had qualified as injectable bone substitute which applied in cases of spinal tuberculosis.